EDUKASI IMUNISASI DASAR LENGKAP PADA IBU DI KELURAHAN TUMAMPUA PANGKAJENE PANGKEP - Balqis, Balqis; Rahmadani, Suci; Saldi, Riangga Putra; Asmudin, Ardayanti; Ramadhany, Fhatira; Mongan, Gabryella Laura; Izzah, Inayatul; Putri, Reski Fadilah (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Immunization is the most effective and efficient public health effort in preventing diseases and reducing mortality rates such as smallpox, polio, tuberculosis, hepatitis B, diphtheria, measles, rubella and congenital rubella syndrome (CRS), tetanus, pneumonia (pneumonia) and meningitis (inflammation of the lining of the brain). The 2020 WHO report states that there are 20 million children who have not received delivery services for toddlers around the world routinely every year. The high number of children who have not been exposed to poison has caused several diseases that can cause paralysis and even death, which should be prevented by vaccines, to reappear in developed and developing countries. These diseases include measles, pertussis, diphtheria and polio. The purpose of this service is to increase the knowledge of mothers in the tumampua sub-district about the depth of complete body weight. This service is carried out in several stages, namely the preparation stage, the implementation stage and the evaluation stage. Complete crush evaluation using a pre-test and post-test questionnaire distributed to participants. The data analysis technique used is the Wilcoxon test. The results showed that counseling about sports was able to increase the knowledge and attitudes of mothers in the Tumampua Village, Kec. Pangkajene, Pangkep Regency